1988
DOI: 10.1073/pnas.85.10.3407
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical coupling in synthetic polypeptides by modulation of an inverse temperature transition.

Abstract: For the polypentapeptide of elastin, (L-Val-L-Pro-Gly-L-Val-Gly The polypeptide ofinterest is the polypentapeptide of elastin, (L-Val-L-Pro-Gly-L-Val-Gly)n, discovered in porcine elastin (1, 2). In bovine elastin, the longest sequence between lysine residues, which can form the cross-links, is 72 residues; for a continuous and unsubstituted sequence of 57 residues, this is the polypentapeptide (3). The synthetic polypentapeptide is soluble in water in all proportions below 250C, but when the temperature is rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 24 publications
0
53
0
Order By: Relevance
“…Urry and co-workers have observed that when the valine in position 4 of (VPGVG) n is replaced in 1 out of 5 pentamers by a glutamic acid residue, the transition temperature shifts from 25°C at both pH 2 and pH 7 to 25°C at pH 2 and 70°C at pH 7. 17 Moreover, this biopolymer also undergoes a pH-modulated contraction and relaxation with a change from higher to lower pH at 37°C. 17 Therefore, the glutamic acidsubstituted (VPGVG) 18 represents an interesting model system for the study of the contributions of polar and nonpolar side chains and their hydration to the conformational states of biopolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Urry and co-workers have observed that when the valine in position 4 of (VPGVG) n is replaced in 1 out of 5 pentamers by a glutamic acid residue, the transition temperature shifts from 25°C at both pH 2 and pH 7 to 25°C at pH 2 and 70°C at pH 7. 17 Moreover, this biopolymer also undergoes a pH-modulated contraction and relaxation with a change from higher to lower pH at 37°C. 17 Therefore, the glutamic acidsubstituted (VPGVG) 18 represents an interesting model system for the study of the contributions of polar and nonpolar side chains and their hydration to the conformational states of biopolymers.…”
Section: Introductionmentioning
confidence: 99%
“…to the less polar COOH moieties). This is because the temperature of the transition is lowered as the polypeptide becomes more hydrophobic, and it is raised as the polypeptide becomes less hydrophobic (16). The molecular interpretation is that the pull of the C00r-moiety to achieve its waters of hydration destructures the waters of hydrophobic hydration, thereby removing the thermodynamic driving force for folding (18).…”
Section: Figurementioning
confidence: 99%
“…Simplicity of the Assay System and efficiency of the ATt Mechanism for Chemomechanical Transduction: For both thermomechanical transduction and chemomechanical transduction, the demonstration of forces developed and work performed can be by means of the simple assay of watching a strip of the cross-linked matrix pick up a weight when the energy source is thermal for thermomechanical transduction (thermally driven folding), or pick up a weight when the energy source is chemical, for example, as when the salt concentration is raised or when the concentration of proton is raised to achieve chemically driven folding (16,17). The forces are obviously real, and they are dramatic with an efficiency, for example, in the conversion of chemical energy into mechanical work that is more than an order of magnitude greater than previously demonstrated for the charge-charge repulsion mechanism of chemomechanical transduction (13).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations